2015
DOI: 10.1038/ni.3141
|View full text |Cite|
|
Sign up to set email alerts
|

Responsiveness of B cells is regulated by the hinge region of IgD

Abstract: Mature B cells express immunoglobulin M (IgM)- and IgD-isotype B cell antigen receptors, but the importance of IgD for B cell function has been unclear. By using a cellular in vitro system and corresponding mouse models, we found that antigens with low valence activated IgM receptors but failed to trigger IgD signaling, whereas polyvalent antigens activated both receptor types. Investigations of the molecular mechanism showed that deletion of the IgD-specific hinge region rendered IgD responsive to monovalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(155 citation statements)
references
References 50 publications
10
143
2
Order By: Relevance
“…31), potentially explaining the unresponsive state of anergic B cells. The intracellular calcium increase elicited by monomeric HEL was directly compared in splenic B cells from MM4 and DD6 transgenic mice, which respectively express the IgM HEL or IgD HEL antigen receptors studied in ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31), potentially explaining the unresponsive state of anergic B cells. The intracellular calcium increase elicited by monomeric HEL was directly compared in splenic B cells from MM4 and DD6 transgenic mice, which respectively express the IgM HEL or IgD HEL antigen receptors studied in ref.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, hen egg lysozyme (HEL) antigen signalling induced CD86 identically through IgD or IgM on splenic B cells expressing one or other isotype21. However, when the same IgM HEL and IgD HEL BCRs were expressed separately in a pro-B cell line with a partially crippled BLNK (SLP65) intracellular signalling adaptor, soluble monovalent HEL antigen signalled an increase in intracellular calcium when it bound IgM but induced no calcium signalling when it bound IgD, whereas multivalent HEL-antigen signalled through both isotypes31. Extrapolating the findings from the BLNK mutant cell line, it was concluded that the predominant expression of IgD on anergic cells prevents any response to monovalent self-antigens, ascribing the in vivo state of anergy to the change in BCR isotype31.…”
mentioning
confidence: 99%
“…It is relevant to point out that the Fab stimulating reagents that are used in these and previously published in vitro studies (815, 18, 19, 45) differ from the ligands that CLL-BCRs encounter in vivo , and that additional characteristics of the stimulating antigen, including affinity (46, 47) and valency (48, 49), may influence the BCR signaling outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The computational investigation of linear peptides with the sequence METPSQRRATRSGAQASSTPLSPTRITRLQ followed an approach similar to earlier work [66]. Three systems were set up in an initial extended conformation, differing in the phosphorylation state of Ser22 and the configuration of Pro23: (1) Ser22 not phosphorylated, Pro23 in trans configuration (Ser22/Pro23 trans ); (2) Ser22 phosphorylated, Pro23 in trans configuration (Ser22 phos/Pro23 trans ); and (3) Ser22 phosphorylated, Pro23 in cis configuration (Ser22 phos/Pro23 cis ).…”
Section: Methodsmentioning
confidence: 99%